Design, Fabrication, and Experimental Implementation of an Automated Trimmer System (International Journal of Communication Systems and Network Technologies, 2022)
This paper presents the design, fabrication, and experimental implementation of an Automated Trimmer System (ATS) developed to improve the efficiency and precision of industrial trimming operations. The system integrates optimized design principles, suitable materials, sensors, and advanced fabrication techniques to achieve reliable performance. Experimental evaluation demonstrates enhanced trimming accuracy, operational efficiency, and adaptability under varying conditions. The proposed ATS offers a cost-effective, robust, and versatile solution for industrial applications, contributing to increased productivity, reduced manual effort, and optimized resource utilization.
Keywords: Automated Trimmer System; Precision Machining; Robotics in Manufacturing; Design Optimization; Fabrication Techniques; Experimental Validation; Industrial Automation; Material Selection; Process Efficiency; Advanced Manufacturing; Trimming Operations; System Integration; Sensor Technology; Performance Evaluation; Innovation in Manufacturing